2012
DOI: 10.1177/1362361312455704
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition, social skill, and the broad autism phenotype

Abstract: Social-cognitive deficits differentiate parents with the "broad autism phenotype" from non-broad autism phenotype parents more robustly than other neuropsychological features of autism, suggesting that this domain may be particularly informative for identifying genetic and brain processes associated with the phenotype. The current study examined whether the social-cognitive deficits associated with the broad autism phenotype extend to the general population and relate to reduced social skill. A total of 74 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
104
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 40 publications
23
104
0
1
Order By: Relevance
“…[46][47][48] Also consistent with the extant literature are our findings showing that ADHD + AT children were more likely than ADHD children to fight with and be rejected by peers, to have more school behavior problems, more difficulties utilizing their spare time, and more problems with siblings. Considering the well-established evidence that social difficulties are a core component of ASDs, [49][50][51] our findings also suggest that the social disability observed in the ADHD + CBCL-AT group may be more a reflection of underlying ATs than the presence of ADHD itself. The higher rates of mood, anxiety, disruptive, and substance use disorders, 52 and school failure, school dropout, and delinquent offenses 53 in ADHD + AT children is particularly worrisome.…”
Section: E618mentioning
confidence: 59%
“…[46][47][48] Also consistent with the extant literature are our findings showing that ADHD + AT children were more likely than ADHD children to fight with and be rejected by peers, to have more school behavior problems, more difficulties utilizing their spare time, and more problems with siblings. Considering the well-established evidence that social difficulties are a core component of ASDs, [49][50][51] our findings also suggest that the social disability observed in the ADHD + CBCL-AT group may be more a reflection of underlying ATs than the presence of ADHD itself. The higher rates of mood, anxiety, disruptive, and substance use disorders, 52 and school failure, school dropout, and delinquent offenses 53 in ADHD + AT children is particularly worrisome.…”
Section: E618mentioning
confidence: 59%
“…The BAPQ contains 36 statements and taps into the domains of aloofness, pragmatic language, and rigidity, which were intended to parallel the three Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition ASD diagnostic domains of social impairment, language impairment, and repetitive behavior. The scale has good reliability and validity (see Hurley et al, 2007;Ingersoll, Hopwood, Wainer, & Donnellan, 2011;Sasson, Nowlin, & Pinkham, 2013) and also correlates well with the AQ and SRS (Ingersoll et al, 2011;Sasson, Nowlin, et al, 2013).…”
Section: Tools For Measuring the Bapmentioning
confidence: 91%
“…On the basis of their results, Losh et al (2009) concluded that BAP + parents resembled individuals with ASD in terms of social cognition, even though their performance was similar to that of BAP − and control parents on measures of executive functioning and central coherence. Sasson, Nowlin, and Pinkham (2012) asserted that impairments in social cognition distinguished BAP + parents from non-BAP parents more consistently than other types of neuropsychological abilities. They sought to learn whether the social cognition deficits of the BAP could be identified in a general population.…”
Section: Social Cognitionmentioning
confidence: 98%
“…They decided to combine scores from two BAPQ subscales, namely the social abnormalities subscale and the pragmatic language subscale, for use as a composite measure of the social BAP. Sasson et al (2012) stated that basic components of social cognition included abilities for face processing, emotion recognition, and ToM. Thus, their investigation included three measures to assess these aspects of social cognition: the Benton Facial Recognition Task (BFRT; Benton et al, 1994), the Penn Emotion Recognition Task (also known as the ER40; Kohler, Bilker, Hagedoorn, Gur, & Gur, 2000), and the Cartoon Theory of Mind test (CTOM; Brunet, Safarti, & Hardy-Bale', 2003).…”
Section: Social Cognitionmentioning
confidence: 99%
See 1 more Smart Citation